Peranan lingkungan sekolah dan keluarga dalam membentuk moralitas peserta didik di era globalisasi - Syakuro, Abdan; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
Technological developments and advances in today's world come with various negative effects, one of which is a decline in student morality that has a negative impact on both personal life and society as a whole. Morality is a principle or standard of behavior used to distinguish between actions that are considered right and wrong from an individual and societal perspective. Education plays a major role in developing students' character, skills, and knowledge. Schools provide opportunities for students to face various challenges in their lives. In this case, the role of teachers is crucial in instilling moral values in students. Teachers are not only tasked with delivering learning materials, but also serve as role models who motivate and guide students through examples of good and proper behavior in accordance with applicable norms. In addition to the role of schools, the contribution of families is also very significant in shaping children's morality. Parents have a responsibility to accompany their children's development from an early age, which is very important for their future and education, as childhood is the most vital time because it forms the foundation of their personality, which can influence their future experiences.